Past and present of the authority of the magistrate in the indigenous political and legal space - Fernández Osco, Marcelo (2002)
This article discusses the progress of some texts and explores the administrative provisions that remodeled the position of corregidor and allowed the State to be strengthened in the various historical moments in the indigenous political and legal space. The changes and continuities of the surviving authority of the corregidor in the long history are examined. Through a procedural and chronological approach, its constitutive moments are highlighted, as well as the distinctive characteristics of its legal and political attributions, product of structural changes.